(untitled) (Research, Society and Development, 2021)
School inclusion is not just limited to placing the student with special needs in the regular class. Therefore, for inclusion to be really effective, it is necessary to have a curriculum suited to your needs and professionals who are properly trained to serve you. This article will discuss the importance of the Inclusive School for human development and for the promotion of sustainable development, addressing the curriculum, practice and daily school life in Inclusive Basic Education. Next, it will address Special and Inclusive Education as being essential for human development. Likewise, it will relate the accuracy of Special and Inclusive Education for sustainable development. As for the methodology, the research will validate the practice of applied and descriptive analysis in relation to its objectives; the qualitative method as to its nature; and bibliographic and documentary methods regarding the procedures for using and collecting data. Therefore, the main objective will be to discuss about inclusive education with emphasis on the curriculum, teaching practice and daily school life, as well as describing the historical triggering and delay in the inclusion of the disabled in society and in regular schools. Consequently, verifying that the existing legislation that promotes the protection of these social rights is insufficient, since the lack of public policies hinders the development of the area in question. In addition, it will seek to verify the accuracy that the Special and Inclusive School presents for the promotion of human, social and sustainable development.